Recent Findings in N6‐Methyladenosine Modification and Significance in Pancreatic Cancer - Tomoaki Hara; Sikun Meng; Yasuko Arao; Yoshiko Saito; Kana Inoue; Sarah Rennie; Ken Ofusa; Toru Kitagawa; Hideshi Ishii (Cancer Medicine)
ABSTRACT Background RNA modifications are widely detected in cells and are involved in RNA structural stabilization and regulation of gene expression. In cancer cells, RNA modifications are altered, resulting in abnormal expression of numerous genes and promoting cancer growth. N1‐methyladenosine (m1A), N6‐methyladenosine (m6A), N3‐methylcytosine (m3C), 5‐methylcytosine (m5C), 7‐methylguanosine (m7G), and N4‐acetylcytidine (ac4C) have been reported as RNA modifications affecting gene expression. Aim In this review, the function of m6A in pancreatic cancer is mainly described, and the current status and prospects of RNA modifications are discussed. Methodology We summarize recent reports on m6A writers METTL3, METTL5, METTL14, and METTL16; m6A readers IGF2BP1, IGF2BP2, IGF2BP3, YTHDF1, YTHDF2, and YTHDF3; and m6A erasers ALKBH5 and FTO. Results RNA modifications are written to the RNA by the writer, and the reader binds to the RNA modification, causing gene expression to increase or decrease. Gene expression is also regulated by the removal of RNA modifications by the eraser. Moreover, our recent investigation into m6A modifications in pancreatic cancer has led to the identification of several promising candidate biomarkers, highlighting the potential role of epitranscriptomic regulation in tumorigenesis. Conclusion These findings suggest that further exploration of RNA modification functions may facilitate the identification of novel biomarker and therapeutic target molecules for pancreatic cancer.